2005
DOI: 10.1056/nejmoa044190
|View full text |Cite|
|
Sign up to set email alerts
|

Independent Clonal Origins of Distinct Tumor Foci in Multifocal Papillary Thyroid Carcinoma

Abstract: Individual tumor foci in patients with multifocal papillary thyroid cancer often arise as independent tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
162
4
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(183 citation statements)
references
References 35 publications
10
162
4
5
Order By: Relevance
“…About 30% of patients with low-risk WDTC harbor contralateral cancers (12,13). While the clinical relevance of these cancers is still unclear, these tumors may represent multicentricity or intrathyroidal spread (14,15). Often these are microcarcinomas that are not detected on preoperative imaging.…”
Section: Figmentioning
confidence: 99%
“…About 30% of patients with low-risk WDTC harbor contralateral cancers (12,13). While the clinical relevance of these cancers is still unclear, these tumors may represent multicentricity or intrathyroidal spread (14,15). Often these are microcarcinomas that are not detected on preoperative imaging.…”
Section: Figmentioning
confidence: 99%
“…avaliaram se focos não contíguos do tumor surgem como metástases de um tumor primário único ou se originam de novos clones com precursores independentes. Os autores concluem que em pacientes com carcinoma papilar multifocal os tumores focais surgem como tumores independentes (16).…”
unclassified
“…However, it is known that papillary thyroid carcinoma occurs frequently as multifocal disease and Shattuck et al showed that these multiple foci PTC's are of different clonal origin [5], similar to non-neoplastic thyroid hyperplasia [6]. This might indicate that the whole thyroid gland, as a field, might be influenced by factors promoting neoplastic transformation, which becomes enhanced when additional growth stimulating factors are present.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is known that PTC often occurs as multifocal disease [2]. Shattuck et al showed that multifocal PTC is, in general, a polyclonal disease and discussed the potential influence of environmental factors on the genesis of PTC [5]. It has been suggested previously that structural aberrations might not be the initiating events in tumorigenesis but may well be subsequent phenomena in proliferating tissue [6].…”
Section: Introductionmentioning
confidence: 99%